Relationship Between Asthma Therapy Types, Pulmonary Function, and Asthma Control in Primary Healthcare Facilities in Medan - Darmawan, Nengah; Tarigan, Amira Permatasari; Pradana, Andika (Journal of Society Medicine, 2025)
Introduction: Asthma is a chronic respiratory disease that affects millions globally. Effective asthma therapy is essential for improving pulmonary function and achieving asthma control. However, many patients remain uncontrolled despite treatment. This study aims to evaluate the relationship between asthma therapy types, pulmonary function, and asthma control in primary healthcare facilities in Medan. Method: This retrospective descriptive study utilized medical records of asthma patients from May 2022 to May 2023 at several primary healthcare centers in Medan. Data collected included demographic characteristics, asthma therapy types (inhaler vs. inhaler + oral), pulmonary function (APE prediction), and asthma control levels. Chi-Square tests were performed to assess statistical associations. Results: The study found that most asthma patients were female (83.3%) and over 50 years old (62.5%). Regarding pulmonary function, 73.0% of patients had an APE prediction of ≥60%, indicating relatively good lung function. However, asthma control remained poor, with 68.8% of patients classified as uncontrolled. The majority of patients (68.8%) used inhalers as their primary therapy, while 31.2% received a combination of inhaler and oral medication. Statistical analysis showed no significant relationship between the type of asthma therapy and pulmonary function (p = 1.000), nor between the type of therapy and asthma control level (p = 0.067). Conclusion: The study found no significant relationship between asthma therapy type, pulmonary function, and asthma control level. These findings suggest that other factors, such as therapy adherence, proper inhaler technique, and medication adjustments, may contribute to asthma control.